2006
DOI: 10.1128/cvi.00213-06
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses of Elk to Initial and Booster Vaccinations withBrucella abortusStrain RB51 or 19

Abstract: Previous studies have suggested that currently available brucellosis vaccines induce poor or no protection in elk (Cervus elaphus nelsoni). In this study, we characterized the immunologic responses of elk after initial or booster vaccination with Brucella abortus strains RB51 (SRB51) and 19 (S19). Elk were vaccinated with saline or 10 10 CFU of SRB51 or S19 (n ‫؍‬ seven animals/treatment) and booster vaccinated with a similar dosage of the autologous vaccine at 65 weeks. Compared to nonvaccinates, elk vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Data suggest that domestic livestock and wildlife reservoirs have diverse immunologic responses to RB51 and S19 vaccines, with differing levels of protection (3,4,6,8,10). In an effort to develop new and more efficacious vaccines, Brucella strains have been generated via recombinant DNA techniques and screened through laboratory animal models.…”
mentioning
confidence: 99%
“…Data suggest that domestic livestock and wildlife reservoirs have diverse immunologic responses to RB51 and S19 vaccines, with differing levels of protection (3,4,6,8,10). In an effort to develop new and more efficacious vaccines, Brucella strains have been generated via recombinant DNA techniques and screened through laboratory animal models.…”
mentioning
confidence: 99%
“…This finding suggests that antigens associated with S19 or RB51 are unable to stimulate proinflammatory elements of the adaptive immune system and appear to be related to failure of immune memory formation (Olsen et al 2006). The elk vaccination studies also showed that elk do, in fact, develop a robust humoral response to vaccination, though some consider the humoral response insufficient to mediate clearance (Olsen et al 2006). The failure of the elk vaccination program in Wyoming has likely allowed Brucella to continue to persist in the Greater Yellowstone area.…”
Section: Discussionmentioning
confidence: 79%
“…Failure of both RB51 and S19 to induce protective memory responses in elk is not well understood and is further confounded by the observation that elk appear to respond initially to vaccination. Despite this observation, analysis of peripheral blood mononuclear cells recovered from vaccinated animals and exposed to c-irradiated S19 or RB51 showed no change in IFN-c production compared to controls (Olsen et al 2006). This finding suggests that antigens associated with S19 or RB51 are unable to stimulate proinflammatory elements of the adaptive immune system and appear to be related to failure of immune memory formation (Olsen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations